2017
DOI: 10.1080/10495398.2017.1395345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single Nucleotide Polymorphisms inIGFBP2andIGFBP3Genes on Litter Size Traits in Berkshire Pigs

Abstract: Litter size is among the most important traits in swine breeding. However, information on the genetics of litter size in pigs is lacking. In this study, we identified single nucleotide polymorphisms (SNPs) in the insulin-like growth factor binding protein 2 and 3 (IGFBP2 and IGFBP3) genes in Berkshire pigs and analyzed their association with litter size traits. The IGFBP2 SNP was located on chromosome 15 intron 2 (455, A > T) and the IGFBP3 SNP was on chromosome 18 intron 2 (53, A > G). The AT type of IGFBP2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Although Berkshire pigs are the most popular with consumers owing to their excellent meat quality, this breed has a smaller litter size than that of the other breeds (Suzuki et al, 2003;Lee et al, 2015). Genetic markers have been developed for improving the litter size traits of Berkshire pigs in a previous study, and the SNPs in IGFBP2 and IGFBP3 are linked to litter size traits in Berkshire pigs (An et al, 2017). However, the previous studies to date have focused on the genetic markers of the Landrace and Large White pig breeds (Kumchoo and Mekchay, 2015;Sell-Kubiak et al, 2015), and the studies on Berkshire pigs are relatively less studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Berkshire pigs are the most popular with consumers owing to their excellent meat quality, this breed has a smaller litter size than that of the other breeds (Suzuki et al, 2003;Lee et al, 2015). Genetic markers have been developed for improving the litter size traits of Berkshire pigs in a previous study, and the SNPs in IGFBP2 and IGFBP3 are linked to litter size traits in Berkshire pigs (An et al, 2017). However, the previous studies to date have focused on the genetic markers of the Landrace and Large White pig breeds (Kumchoo and Mekchay, 2015;Sell-Kubiak et al, 2015), and the studies on Berkshire pigs are relatively less studied.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-Seq was performed with isolated RNA as previously described by Jung et al (2012). RNA variations were identified based on the pig genome database using the RNA-DNA difference method (An et al, 2017). The SNPs were detected by assembling and mapping raw data to UniGene (https: //www.ncbi.nlm.nih.gov/unigene, last access: August 2017), and the information of the detected SNPs obtained using the dbSNP database of NCBI 0 (rs55620935 for MAP3K3 and rs334957540 for NAT9).…”
Section: Snp Detection By Rna-seqmentioning
confidence: 99%
See 1 more Smart Citation
“…IGFBP2, a key member of the IGF family, is present in follicular fluid and subject to dynamic changes during follicle growth and maturation (Spitschak & Hoeflich, ). Previous reports have confirmed the involvement of genetic variants of IGFBP2 in reproductive traits or litter size in different pig populations (An et al, ) and age at first calving in dairy cattle (Clempson, Pollott, Brickell, & Wathes, ). Moreover, mRNA expression analysis showed that IGFBP2 mRNA level was upregulated in the endometrium of pregnant mares (Merkl et al, ) and of pigs (Ostrup, Bauersachs, Blum, Wolf, & Hyttel, ) on day 14 of pregnancy.…”
Section: Discussionmentioning
confidence: 68%
“…Gene editing tools are therefore expected to play a key role in both genetic improvement by targeted genetic variation and also in the study of pig genome annotation. [59] APOA2 Fatty acid composition c.I199V [36] PRKAG3 Meat quality c.T30N [36] PRKAG3 Meat quality g.8227C > G [60] MUC4 Production traits c.C2604T [61] PIK3C3 Production traits g.A53G [62] IGFBP3 Litter size g.35547A > G [63] ESR2 Sperm motility g.158 A > C [64] PLCz Sperm concentration g.358A > T [65] CD9 Sperm motility g.C7462G [66] CXCL12 Pseudorabies virus disease resistance c.12164 + 79G > A [66] BAT2 Immunological traits c.86172 + 140C > T [66] Mx1…”
Section: Snps Responsible For Disease Resistancementioning
confidence: 99%